Analisis Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di Sma Negeri 4 Singaraja Tahun 2020 - Kadek Gita Puspita Saisarani; Ni Kadek Sinarwati (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aimed to know (1) the planning, implementation, supervision, and reporting process of Dana BOS (the fund of School Operational Assistance) Management (2) the obstacles faced in managing Dana BOS in SMA Negeri4 Singaraja in 2020 as well as the efforts to overcome its obstacles. The research approached used was a descriptive qualitative approach. The data collection was done through observation, interview and documentation study. The data analysis used in this study were data reduction, data presentation, and conclusion drawing. The results show that 1) the planning, implementation, supervision, and reporting process of Dana BOS Management in SMA Negeri 4 Singaraja in 2020 has run well according to the technical guidelines of Permendikbud (Ministerial Regulation of Education and Culture) Number 8 of 2020, 2) the obstacles in managingDana BOS in SMA Negeri 4 Singaraja were the disbursement of funds was often delayed and there were also regulation changes in the School Operational Assistancemanagement. The efforts undergone to overcome the obstacles were done by the management team in SMA Negeri 4 Singaraja who have to borrow loans from the corporate partner and related to the changes in the government regulations, the financial management team re-compile LPJ (the accountability report) according to the new Permendikbud technical instructions.